Ethnomathematic Analysis: Geometry in Silk Woven Sarongs - Quraisy, Andi; Nursakiah, Nursakiah; Mutmainnah, Mutmainnah (Universitas Negeri Makassar, 2025)
This study aims to explore geometric concepts in the motifs of Wajo silk woven sarongs (lipa' sabbe) through an ethnomathematics approach. The method used is exploratory with an ethnographic approach to reveal the mathematical values contained in local cultural heritage. The results of the study show that woven sarong motifs contain various geometric concepts such as symmetry (reflection, rotation), transformation (translation), and basic geometric shapes (squares, rhombuses, triangles). Each sarong motif represents mathematical principles that can be explained through the Cartesian coordinate system and isometric transformations. This study demonstrates that traditional weaving is not only an expression of cultural art but can also serve as an educational medium in contextual mathematics learning based on local culture. The integration of ethnomathematics in education is expected to enhance students' understanding of abstract mathematical concepts and foster appreciation for regional culture.